2003
DOI: 10.1093/cercor/13.7.793
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Haemodynamic Correlates of Face Perception, Recognition and Priming

Abstract: Face perception, recognition and priming were examined with event-related functional magnetic resonance imaging (fMRI) and scalp event-related potentials (ERPs). Face perception was associated with haemodynamic increases in regions including bilateral fusiform and right superior temporal cortices, and a right posterior negativity (N170), most likely generated in the superior temporal region. Face recognition was associated with haemodynamic increases in fusiform, medial frontal and orbitofrontal cortices, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
260
4
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 359 publications
(316 citation statements)
references
References 73 publications
51
260
4
1
Order By: Relevance
“…The KDEF has been validated as a reliable facial set and used in a number of emotion studies (Goeleven et al, 2008). Additionally, 63 scrambled versions of the KDEF faces were used in the task as non-facial controls (Henson et al, 2003). Overall, the task consisted of 315 trials, substantially more than previous emotion perception studies, but a necessary requirement for ERP analyses, divided into 3 blocks of 105 trials each, with a brief break in between blocks.…”
Section: Facial Expression Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…The KDEF has been validated as a reliable facial set and used in a number of emotion studies (Goeleven et al, 2008). Additionally, 63 scrambled versions of the KDEF faces were used in the task as non-facial controls (Henson et al, 2003). Overall, the task consisted of 315 trials, substantially more than previous emotion perception studies, but a necessary requirement for ERP analyses, divided into 3 blocks of 105 trials each, with a brief break in between blocks.…”
Section: Facial Expression Taskmentioning
confidence: 99%
“…Conversely their origins may lie in the neural structures underlying perceptual and emotional processing of facial expression stimuli (Gray et al, 2007, Henson et al, 2003. Self-report questionnaires provide insight into self-assessed emotional responsiveness, which in some HD studies have shown trends and significance for lower self-assessed emotion (Sprengelmeyer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used data from a single subject and from one channel, PO8, which showed an N170 component in response to face stimuli [Henson et al, 2003]. We computed the average (ERP) and the singular value decomposition (SVD) of the sample residual covariance matrix.…”
Section: Synthetic Datamentioning
confidence: 99%
“…We tested our algorithm on the EEG response to 380 seeing faces as compared to scrambled faces. In this paradigm we know from fMRI studies (Henson et al, 2003) and combined EEG/MEG studies (Henson et al, 2009) that the activated areas include the FFA and OFA. Studies of patients with lesions in the FFA and OFA further validate the importance of these areas in face perception (Eimer and McCarthy, 1999;Dalrymple et al, 2011).…”
mentioning
confidence: 99%